Methods of processing of some under-utilized yam and cocoyam tuber varieties: effect on carotenoid content - Ukom, A.N.; Ojimelukwe, P.C.; Alamu, Emmanuel Oladeji (2016)
Identification and quantification of carotenoids from yam and cocoyam were evaluated after different processing methods. Seven carotenoids were identified by HPLC-DAD both in the raw and processed tubers. The mean carotenoids in yam, D. cayenensis was α-carotene (0.78 μg/g), 9-cis-β-carotene (0.71 μg/g), all-trans-β-carotene (1.28 μg/g); in D. bulbifera was lutein (1.53 μg/g), 9-cis-β-carotene (0.39 μg/g), all-trans-β-carotene (0.19 μg/g). Cocoyam, X. maffa (Scoth) had lutein (0.95 μg/g), α-carotene (1.35 μg/g), 9-cis-β-carotene (0.78 μg/g) and all-trans-β-carotene (1.91 μg/g). The impact of methods of processing show that the loss of 9-cis-β-carotene and/or all-trans β-carotene in the boiled process was associated with increase in 13-cis-β-carotene in the yam/cocoyam samples. Roasted method show minimal loss of carotenoids when compared with fried and oven-dried methods. Mean percentage retention of total carotenoids after processing was boiling (80.1%), roasting (79%), oven-drying (24.51%) and frying (15%). There was relative good retention of total carotenoids in the boiled and roasted process to improve human nutrition.